THE MEANING OF TINGKA RITUALS IN SHIFTING CULTIVATION OF MUNA COMMUNITY SOUTHEAST SULAWESI, INDONESIA - Ali Basri, La Ode; Marhadi, Akhmad; ., Hisna; ., Fatma; ., Fetni (E-Journal of Cultural Studies; Vol 16 No 1 (2023): Volume 16 Number 1 February 2023, 2023)
Most of the Muna community are shifting cultivators who are very dependent on their natural environment, so they  always adapt and interact with nature. One of the media used to adapt and interact with nature is ritual tingka . In  practice, the ritual tingka contains symbolic messages for nature conservation and a form of human appreciation for  nature, flora, and fauna as a whole. The objective of this study was to study and analyze the ecological wisdom of  shifting cultivation related to land conservation and the form of human appreciation for nature through farming  rituals. This study used a normative survey method which was carried out in seven villages in Muna regency,  Southeast Sulawesi. Data collection was conducted through in-depth interviews, observation, and focus group  discussions. The collected data were analyzed using flow analysis techniques. The results showed that symbolically  the tingka ritual was the institutionalization of knowledge of land conservation through agro forestry patterns, namely by combining the planting of trees such as bamboo, areca nut, kapok with food and secondary crops. Ritual  tingka is a form of respect for nature to create a harmonious relationship between the microcosm and the  macrocosm, so that farmers are protected from various disasters. Keywords : Shifting cultivation; rituals Itingka; ethnoecology;   and Muna community